Peste Des Petits Ruminants (PPR) in Dromedary Camels and Small Ruminants in Mandera and Wajir Counties of Kenya - R. N. Omani; G. C. Gitao; J. Gachohi; P. K. Gathumbi; B. A. Bwihangane; K. Abbey; V. J. Chemweno (Advances in Virology)
A study was conducted to determine the presence of Peste des petits ruminants (PPR) in camel population kept together with small ruminants in Isiolo, Mandera, Marsabit, and Wajir counties of Kenya. This was done in the wake of a disease with unknown etiology “Camel Sudden Death Syndrome” camels in the horn of Africa. Thirty-eight (38) samples, 12, 8, 15, and 3 samples, were collected from Mandera, Wajir, Isiolo, and Marsabit, respectively, from 25 camels, 7 goats, and 4 sheep. One camel in Mandera and one goat in Wajir were confirmed positive for PPR virus (PPRV) through reverse Polymerase Chain Reaction. The analysis of sequences revealed closest nucleotide identities of obtained sequences from both goat and camel to the lineage III of PPRV albeit with 60.29% of nucleotide identity. This study establishes that camels in the study area suffer with PPR manifest clinical signs that are mainly characterized by inappetence, loss of body condition, and general weakness terminally leading to diarrhea, conjunctivitis, and ocular nasal discharges preceding death. These clinical signs are similar to those observed in small ruminants with slight variations of manifestations such as keratoconjunctivitis as well as edema of the ventral surface of the abdomen. This shows that camels could be involved in the epidemiology of PPR in the region and that PPRV could be involved in the epidemics of Camel Sudden Death syndrome. There is therefore a need for resources to be dedicated in understanding the role camels play in the epidemiology of PPR and the role of the disease in Camels Sudden death syndrome.